Environmental justice and rural communities : studies from India and Nepal - Vani, M. S.; Asthana, Rohit; Belbase, Narayan; Thapa, L. B.; Moore, Patricia, 1949-; Pastakia, Firuza (International Union for Conservation of Nature and Natural Resources : Available from the World Conservation Union, Asia Regional Office, 2007)
Contributed articles.